2018
DOI: 10.3390/ma11071194
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of p-Type Sb2Te3 Films and Micro-Pillar Arrays in a Multi-Channel Glass Template

Abstract: Antimony telluride (Sb2Te3)-based two-dimensional films and micro-pillar arrays are fabricated by electrochemical deposition from electrolytes containing SbO+ and HTeO2+ on Si wafer-based Pt electrode and multi-channel glass templates, respectively. The results indicate that the addition of tartaric acid increases the solubility of SbO+ in acidic solution. The compositions of deposits depend on the electrolyte concentration, and the micro morphologies rely on the reduction potential. Regarding the electrolyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, the deposition of p-type Sb 2 Te 3 was limited because that SbO + has poor solubility in acidic solution, which leads to poor crystallization, nonstoichiometry and low density of the sample, and weak TE properties of the pillar. In our work, it is found that the addition of tartaric acid could increase the solubility of SbO + [41]. The composition of deposits can be adjusted by the electrolyte concentration.…”
Section: Resultsmentioning
confidence: 67%
“…However, the deposition of p-type Sb 2 Te 3 was limited because that SbO + has poor solubility in acidic solution, which leads to poor crystallization, nonstoichiometry and low density of the sample, and weak TE properties of the pillar. In our work, it is found that the addition of tartaric acid could increase the solubility of SbO + [41]. The composition of deposits can be adjusted by the electrolyte concentration.…”
Section: Resultsmentioning
confidence: 67%
“…Density function theory (DFT) has been adopted to calculate the lattice constants and electronic structures of BiCuOCh (Ch = Se, S) under strain constraint, which are implemented in the Vienna ab initio Simulation Package (VASP) [23][24][25][26]. The projector augmented wave (PAW) method is chosen with Perdew-Burke-Ernzerhof (PBE) generalized gradient approximation (GGA) exchange-correlation potential [27].…”
Section: Computational Detailsmentioning
confidence: 99%